Religion, the first amendment, and public schools : stories from K-12 and teacher education classrooms - Bodle, Aaron; Saylor, Elizabeth E.; Bellows, Elizabeth (Educator); An, Sohyun; Buchanan, Lisa Brown (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
"White Christian Nationalism is "an ideology that seeks to idealize and advocate a fusion of American Civic life with a... White Christian ethnoculture" rooted in traditionalism, anti-immigration, and their judicial codification (Gorski & Perry, 2021). Though the establishment clause clearly delineates a boundary between religion and state. Despite the clarity of this division in the Establishment Clause, this bedrock of our democracy has faced near-constant pressure from Christian right. Recently, this pressure has taken the form of strategic efforts to stack the Supreme Court of conserative judges and control local school boards by waging fear and misinformation campaigns. Political division, a lack of healthy discourse about religious diversity, and misunderstandings about the Establishment Clause have left many educators unsure about their role in valuing religious diversity in their schools and classrooms, and their responsibilities to maintain religious freedom for all students"--